A Room of His Own : A Literary-Cultural Study of Victorian Clubland - Black, Barbara J., 1962- (Book collections on Project MUSE., 2012)
In nineteenth-century London, a clubbable man was a fortunate man, indeed. The Reform, the Athenaeum, the Travellers, the Carlton, and the United Service are just a few of the gentlemen's clubs that formed the exclusive preserve known as "clubland" in Victorian London - the City of Clubs that arose during the Golden Age of Clubs. Why were these associations for men only such a powerful emergent institution in nineteenth-century London? Distinctly British, how did these single-sex clubs help fashion men, foster a culture of manliness, and assist in the project of nation building? What can elite male affiliative culture tell us about nineteenth-century Britishness? This book sheds light on the mysterious ways of male associational culture as it examines such topics as fraternity, sophistication, nostalgia, social capital, celebrity, gossip, and male professionalism.